Effect of the Bailey Ratios in Superpave Gradation Design for Tokyo International Airport Pavement - Teck Shang Goh; Osamu Takahashi; Ryota Maekawa (The Baltic Journal of Road and Bridge Engineering, 2013)
This paper discusses the use of the Bailey method in Superpave mixture design for Tokyo International Airport (HND) pavements. The objective of this study is to determine whether the fine graded gradations with 70% of loose unit weight of coarse aggregate will produce the mixtures that meet the Superpave requirements and provide high rutting resistance compared to the current HND Marshall mixture. Ten gradations with the recommended upper and lower limits of the Bailey ratios were designed. The effect of the Bailey ratios on voids in mineral aggregate (VMA) and rutting resistance of the mixture was examined. Rutting resistance of each specimen was evaluated by Asphalt Pavement Analyzer (APA). The experimental results showed that the current Bailey recommended limits have to be adjusted to a narrow range. The mixture with the mean values of the Bailey recommended limits had adequate VMA and better resistance to rutting.